Investigation of Life Cycle Cost (LCC) data inputs of flexible pavement in Klang Valley - Bidi, Nor Khalisah; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2015)
There are two types of pavement, i.e. rigid and flexible pavements. Flexible pavement is the pavement that composed of a number of layers. The upper layers are generally made up of material using bitumen as a binder, and the lower layers are made up of granular materials. Life Cycle Cost (LCC) is an assessment technique that estimates all cost related to the ownership of an asset and compares the overall long-term economic efficiency between the available competing alternatives in order to provide significant cost savings. However, there is the limitation in implementing LCC analysis where very little emphasize is on the availability, accessibility, currency and reliability of data as inputs into the process of producing reliable LCC outputs. The objective of this research is to present a proposal of study on investigation of quality of cost data input of LCC analysis and develop strategies to improve the quality of data input in LCC analysis of flexible pavement. The methodology proposed for the study is a qualitative research strategy that comprises of two approaches, which are literature review (secondary data) and focus group discussion (primary data). The outcome of the study is a guideline that provides methodology to identify the quality cost data and to improve the quality of cost data of LCC analysis of flexible pavement in the Malaysian construction industry.